An Assessment of Judges' Self‐Reported Experiences of Secondary Traumatic Stress. (6th June 2019) - Edwards, Charles P.; Miller, Monica K.
Abstract: Many judges experience occupation‐specific stress, such as secondary traumatic stress (STS), burnout, compassion fatigue, and vicarious traumatization. A content analysis of 762 judges' open‐ended responses to a survey asking whether they had suffered from STS revealed that judges moderately experienced most types of stress. Some case types (e.g., family court) and some job aspects (e.g., gruesome evidence) were particularly stressful. Judges reported both positive (e.g., social support) and negative (e.g., distractions) coping mechanisms. Interventions should be tailored to judges' characteristics, (e.g., gender), job (e.g., family court), beliefs (e.g., that STS does not exist), and level of distress.